My First Year Journey from TV News Anchor to Tengku Permaisuri Selangor An Anecdotal Experience - Norely Abdul Rahman Datin (Jugra Publications, 2019)
My First Year Journey, from TV News Anchor to Tengku Permaisuri Selangor is an insight into the first year of Her Royal Highness, Tengku Permaisuri Norashikin as a member of the royal family. Revealing personal reflections and thoughts, this book shares fascinating details of Her Royal Highness' life that has never been disclosed to the public before.